The Use of Self-Managed Treatment Strategies in a Predominantly Low-Income, African-American Sample of Women Living with HIV. Issue 3 (June 2015) - Houston, Eric; Osborn, Amanda
While low-income and ethnic minority women represent a growing proportion of new HIV cases in the United States, little is known about how they manage their antiretroviral medication regimens. Using a predominantly low-income, African-American sample ( N = 85), this study examined medication self-management strategies among HIV seropositive women undergoing antiretroviral therapy in a major metropolitan area. Most study participants (95%; n = 81) reported employing a specific medication management strategy during the previous week. Pillboxes, use of daily activities, and receiving reminders from another person were the most common strategies. Most participants (80.2%) employed two or more strategies. Age, education, and motivation were associated with alarm, pillbox, and visual aid usage.